A partial economic evaluation of blended learning in teaching health research methods: a three-university collaboration in South Africa, Sweden, and Uganda. Issue 1 (1st December 2016) - Kumpu, Minna; Atkins, Salla; Zwarenstein, Merrick; Nkonki, Lungiswa
Abstract : Background: Novel research training approaches are needed in global health, particularly in sub-Saharan African universities, to support strengthening of health systems and services. Blended learning (BL), combining face-to-face teaching with computer-based technologies, is also an accessible and flexible education method for teaching global health and related topics. When organised as inter-institutional collaboration, BL also has potential for sharing teaching resources. However, there is insufficient data on the costs of BL in higher education. Objective: Our goal was to evaluate the total provider costs of BL in teaching health research methods in a three-university collaboration. Design: A retrospective evaluation was performed on a BL course on randomised controlled trials, which was led by Stellenbosch University (SU) in South Africa and joined by Swedish and Ugandan universities. For all three universities, the costs of the BL course were evaluated using activity-based costing with an ingredients approach. For SU, the costs of the same course delivered with a classroom learning (CL) approach were also estimated. The learning outcomes of both approaches were explored using course grades as an intermediate outcome measure. Results: In this contextually bound pilot evaluation, BL had substantially higher costs than the traditional CL approach in South Africa, even when average per-site or per-student costs were considered. Staff costs were the major cost driver in both approaches, but total staff costs were three times higher for the BL course at SU. This implies that inter-institutional BL can be more time consuming, for example, due to use of new technologies. Explorative findings indicated that there was little difference in students' learning outcomes. Conclusions: The total provider costs of the inter-institutional BL course were higher than the CL course at SU. Long-term economic evaluations of BL with societal perspective are warranted before conclusions on full costs and consequences of BL in teaching global health topics can be made.